The effect of pretreatment process on lignocellulosic materials with a combination of microwaves and alkaline solvents on solid products. - Medya Ayunda Fitri; Yulia Tri Rahkadima (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
The pretreatment process is important in treating lignocellulosic-rich biomass such as sugarcane bagasse. The lignocellulosic structure is strong, and the proportion of crystals is high, complicating the fermentation process. Still, it needs to be converted to a more amorphous structure for easy access to fermenting enzymes. The pretreatment process is carried out with alkaline solvents and microwaves in this study. The process begins by standardizing the size of the bagasse powder used. Sugarcane bagasse powder and NaOH alkaline solvent were mixed in a three-necked round-bottom flask. The reactor used in this study was a modified domestic microwave equipped with a temperature controller and condenser. The results showed that this modification was significant to reduce the weight of the residual solid product compared to the initial weight of the raw material. Process variables such as reaction time and solvent concentration significantly affect the cellulose content of solid products. However, hemicellulose content showed different results. The results of the XRD analysis showed that the crystallization index of the effect decreased with increasing pretreatment time. Pretreatment with microwaves and alkaline solvents was successful with satisfactory structural changes in the cellulosic solid.